The growth of iRadio OUM as a quality audio learning material provider - Umi Hanim Mohd Ibrahim; Fathinirna Mohd Arshad; Mazlan Zulkifly; Woo, Janet Tai Kwan (Emerald Group Publishing, 2016)
Purpose : The purpose of this paper is to discuss the progress of iRadio OUM over the years, the evolution of technology used and its overall significance to OUM’s continual growth and development.